A Literature Review On The Impact Of Perceived Organizational Support On Work Meaningfulness, Engagement, And Perceived Stress - Krismanto, Didik; Saluy, Ahmad Badawi; Perkasa, Didin Hikmah (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the influence of perceived organizational support (POS) on meaning of work, employee engagement, and the level of stress experienced, using a Systematic Literature Review (SLR) approach. This review involved 15 scientific articles published between 2019 and 2024, focusing on the relationship between perceptions of organizational support and employee work experiences. The results of this review indicate that POS plays a significant role in increasing the meaning of work and employee engagement, and also acts as a buffer against work stress. Employees who feel supported by the organization tend to show higher loyalty, intrinsic motivation, and professional commitment, which in turn has a positive impact on their performance and well-being. The findings also indicate that employee engagement acts as a mediator in the relationship between meaning of work and stress, while factors such as ethical climate and organizational culture can strengthen the impact of POS. This study emphasizes the importance of managerial strategies that focus on employee support, recognition, and empowerment to create a healthy and productive work environment.